(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
Turkish endemic taxon Onopordum bracteatum Boiss. & Heldr. var. arachnoideum Erik & Sümbül is transferred to O. myriacanthum Boiss. as O. myriacanthum subsp. arachnoideum (Erik & Sümbül) P?nar & Behçet comb. & stat. nov. It is characterized by the phyllaries with densely and persistently arachnoid hairs both inside and outside, and upper stem leaves are 28 cm far from capitulum. In addition, the pollen characteristics and achene features are presented. The conservation status of O. myriacanthum subsp. arachnoideum has been assessed according to IUCN criteria. A distribution map of O. myriacanthum subsp. arachnoideum and its related taxa is also presented. DOI: http://dx.doi.org/10.3329/bjpt.v21i2.21352 Bangladesh J. Plant Taxon. 21(2): 139-145, 2014 (December)